Two-pore-domain potassium (K2P-) channels: cardiac expression patterns and disease-specific remodelling processes - Wiedmann, Felix Tobias; Frey, Norbert; Schmidt, Constanze (Cells, 2021)
Two-pore-domain potassium (K2P-) channels conduct outward K+ currents that maintain the resting membrane potential and modulate action potential repolarization. Members of the K2P channel family are widely expressed among different human cell types and organs where they were shown to regulate important physiological processes. Their functional activity is controlled by a broad variety of different stimuli, like pH level, temperature, and mechanical stress but also by the presence of lipids or pharmacological agents. In patients suffering from cardiovascular diseases, alterations in K2P-channel expression and function have been observed, suggesting functional significance and a potential therapeutic role of these ion channels. For example, upregulation of atrial specific K2P3.1 (TASK-1) currents in atrial fibrillation (AF) patients was shown to contribute to atrial action potential duration shortening, a key feature of AF-associated atrial electrical remodelling. Therefore, targeting K2P3.1 (TASK-1) channels might constitute an intriguing strategy for AF treatment. Further, mechanoactive K2P2.1 (TREK-1) currents have been implicated in the development of cardiac hypertrophy, cardiac fibrosis and heart failure. Cardiovascular expression of other K2P channels has been described, functional evidence in cardiac tissue however remains sparse. In the present review, expression, function, and regulation of cardiovascular K2P channels are summarized and compared among different species. Remodelling patterns, observed in disease models are discussed and compared to findings from clinical patients to assess the therapeutic potential of K2P channels.
Gesehen am 22.12.2021
This article belongs to the special issue "Electrical remodeling in cardiac disease"
Im Titel ist "2P-" tiefgestellt